O que as mães da Geração Z estão procurando?: um estudo sobre o consumo nas práticas de baby care - Moura, Douglas Antonio Tavares de (2022)
Nowadays, we see that there are several generations of “parents” in society that have been shaped over the years, however, for all these generations, the birth of a new baby ends up not only representing a new affective cycle, but also a new investment cycle. In view of this, we observe that the consumption of Baby Care in Brazil, which includes a wide range of products such as diapers, shampoos, Liquids Soaps and Rash creams has been growing at a fast pace and this category is expected to reach a level of 6.1 billion reais in 2021 according to the Euromonitor survey (2019). However, this growth has also been accompanied by changes in the consumption practices of the different parental generations that have witnessed the great evolution of mass information and entertainment on the internet, television, video game and mainly, technological devices, especially mothers of generation Z, focus of this study. To investigate the consumption practices focused on children's shampoo and liquid soap of mothers of this generation, the Theories of Practice were activated, a promising theoretical lens for this research, as it understands consumption as an integral part of practices. Methodologically, it was opted for a qualitative research of exploratory nature with a semi-structured questionnaire and a complementary research, through an iconographic approach through the survey of print ads from the Baby Care universe of the past decades. For the analyses, content analysis was used, seeking to classify themes or categories that help to understand what is behind the sayings, actions and feelings involved in parenting practices. As a result, it is concluded that different from what we saw in previous generations observed in the literature, generation Z is a generation where mothers are more practical, want quick information, are active in the digital universe and have a strong tendency to be influenced mainly by professionals from the health as doctors. Mothers of this generation are initially extremely dependent on previous generations in relation to parenting skills such as the act of cleaning their children. In addition, the practice of consumption for them goes far beyond the simple act of purchase, they seek self-satisfaction through the attributes of quality and performance, that is, the price is no longer a decision-making factor in the purchase. Another interesting point is that generation Z mothers have no connection with Baby care brands, but they trust traditional, natural brands that are well evaluated and recommended by health professionals, other mothers and digital influencers. Finally, it is seen that these mothers identify with brands that have a value purpose such as caring for the planet, society, nature, diversity and inclusion and value brands that convey what they really need to know about the product, as brands that invest in campaigns with purely sentimental appeal can no longer generate experimentation.